2021
DOI: 10.1175/bams-d-19-0070.1
|View full text |Cite
|
Sign up to set email alerts
|

C-FOG: Life of Coastal Fog

Abstract: Capsule: A comprehensive multidisciplinary research program on coastal fog provides unique insights on its lifecycle and predictability barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 70 publications
1
52
0
Order By: Relevance
“…Recent fog field programs, including LANFEX in the UK, SoFog 3-D (https://www.umr-cnrm.fr/ spip.php?article1086&lang=fr{#}outil_sommaire_0, last access: 2 October 2021) in France and studies in India and China, have focused on fog over land but are providing valuable field data for model comparisons. The C-Fog campaign (Fernando et al, 2021) is providing valuable data on coastal fog, and the 2021-2026 Fatima (Fog and Turbulence Interactions in the Marine Atmosphere; https://efmlab.nd.edu/ research/Fatima/, last access: 2 October 2021) project will be a major contribution to the understanding of marine fog.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent fog field programs, including LANFEX in the UK, SoFog 3-D (https://www.umr-cnrm.fr/ spip.php?article1086&lang=fr{#}outil_sommaire_0, last access: 2 October 2021) in France and studies in India and China, have focused on fog over land but are providing valuable field data for model comparisons. The C-Fog campaign (Fernando et al, 2021) is providing valuable data on coastal fog, and the 2021-2026 Fatima (Fog and Turbulence Interactions in the Marine Atmosphere; https://efmlab.nd.edu/ research/Fatima/, last access: 2 October 2021) project will be a major contribution to the understanding of marine fog.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many field measurements in marine fog, including, notably, Geoffrey Ingram Taylor's (1917) work over the Grand Banks and, more recently, the C-Fog study reported by Fernando et al (2021). As far as we are aware, none have provided the Q c (z) profile data from which we could make z 0c determinations.…”
Section: Past Field and Laboratory Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-FOG field project lasted from 25 August to 8 October 2018. A full overview of C-FOG, including the observation sites and instrumentation, is given in Fernando et al (2021). Ferryland contained three sites with visibility measurements using Vaisala PWD22 or PWD52 present weather detectors (Gultepe et al 2021).…”
Section: Measurements Field Project and Analysismentioning
confidence: 99%
“…There have been many field measurements in marine fog, including, notably, G.I. Taylor's (1917) work over the Grand Banks, and more recently the C-Fog study reported by Fernando et al (2021). As far as we are aware none have provided the Qc(z) profile data from which we could make z0c determinations.…”
Section: Past Field and Laboratory Measurementsmentioning
confidence: 99%